(3fTQ GdeMGSf GdZGdjI aj aVd eTGjN GdUhajI Chdi GdebGeGJ GdYGdjIs - (3GdjGaYj , Yaja GdOjf YHO Gddg Hf CSYO Hf Ydj GdjGaYj Gdjefj, Yaja GdOjf,J (B768 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CMjG HPcQg bdhH GhdjGFg s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B72 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B34s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B177 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B11 - (3U (B279 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs